2006
DOI: 10.1159/000091726
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Disease: The Quest for Magic Bullets

Abstract: Lyme disease represents a growing public health threat. Recent molecular and genetic studies have confirmed that Borrelia burgdorferi, the spirochetal agent of Lyme disease, is one of the most complex bacteria known to man. Affinity for multiple cell types and the presence of non-replicating forms of B. burgdorferi have contributed to persistent infection and failure of simple antibiotic regimens. The controversial clinical science of Lyme disease has impeded reliable diagnosis and effective treatment of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 140 publications
0
2
0
1
Order By: Relevance
“…Jak stwierdzają R.B. Stricker, A. Lautin, J.J. Burrascano [46], jedną z istotnych przyczyn kontrowersji dotyczących leczenia boreliozy jest brak wiarygodnych testów, dzięki którym byłoby możliwe monitorowanie leczenia i określenie momentu wyleczenia oraz obecności koinfekcji, które mogą komplikować przebieg choroby. W Stanach Zjednoczonych borelioza, choroba przenoszona przez krętki Borrelia burgdorferi, jest najczęstszą chorobą w kraju.…”
Section: Cel Pracyunclassified
“…Jak stwierdzają R.B. Stricker, A. Lautin, J.J. Burrascano [46], jedną z istotnych przyczyn kontrowersji dotyczących leczenia boreliozy jest brak wiarygodnych testów, dzięki którym byłoby możliwe monitorowanie leczenia i określenie momentu wyleczenia oraz obecności koinfekcji, które mogą komplikować przebieg choroby. W Stanach Zjednoczonych borelioza, choroba przenoszona przez krętki Borrelia burgdorferi, jest najczęstszą chorobą w kraju.…”
Section: Cel Pracyunclassified
“…Thus, LB represents a growing public health threat in the world [ 3 , 8 ]. Recent molecular and genetic studies have confirmed that B. burgdorferi , the spirochetal agent of LB, is one of the most complex bacteria known [ 15 ]. This should alert all physicians to take into account the presence of Lyme neuroborreliosis in southern Bosnia and Herzegovina as a new problem for epidemiologists and other physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This could avoid long-term, and therefore potentially side-effect-prone, antibiotic treatment. As can be expected, there is a lot of controversy on the subject of chronic Lyme disease [29,62,68]. …”
Section: Current Treatment Of Lyme Diseasementioning
confidence: 99%